Dār al-‘Ahd wa al-Shahādah: Muhammadiyah’s Position and Thoughts on Negara Pancasila - Hasnan Bachtiar (Studia Islamika, 2020)
This paper evaluates Muhammadiyah’s effort to revitalise the doctrine of Siyar since the publication of Negara Pancasila sebagai Dār al-‘Ahd wa al-Shahādah (the state of Pancasila as the abode of covenant and the space of testimony). It finds that the ideas in the publication aim to provide guidance for Muhammadiyah members on the relationship between the state and Muhammadiyah. It ensures that its members will understand that Indonesia is Dār al-‘Ahd wa al-Shahādah. It seeks to defend itself against Islamist criticism, while also affirming its responsibility for state development. This paper argues that the idea is a product of Muhammadiyah’s contemporary ijtihad, an effort in theologising democracy based on the idea of Islam Berkemajuan (Islam with progress), in order to strengthen the social bonds of its members who are facing the challenging reality of the massive spread of Islamism and the associated social, political and economic problems.